Surface-Initiated Atom Transfer Polymerized Anionic Corona on Gold Nanoparticles for Anti-Cancer Therapy - Wei Mao; Sol Lee; Ji Un Shin; Hyuk Sang Yoo (MDPI AG, 2020)
Surface initiated atom transfer radical polymerization (SI-ATRP) documented a simple but efficient technique to grow a dense polymer layer on any surface. Gold nanoparticles (AuNPs) give a broad surface to immobilize sulfhyryl group-containing initiators for SI-ATRP; in addition, AuNPs are the major nanoparticulate carriers for delivery of anti-cancer therapeutics, since they are biocompatible and bioinert. In this work, AuNPs with a disulfide initiator were polymerized with sulfoethyl methacrylate by SI-ATRP to decorate the particles with anionic corona, and branched polyethyeleneimine (PEI) and siRNA were sequentially layered onto the anionic corona of AuNP by electrostatic interaction. The in vitro anti-cancer effect confirmed that AuNP with anionic corona showed higher degrees of apoptosis as well as suppression of the oncogene expression in a siRNA dose-dependent manner. The in vivo study of tumor-bearing nude mice revealed that mice treated with c-Myc siRNA-incorporated AuNPs showed dramatically decreased tumor size in comparison to those with free siRNA for 4 weeks. Furthermore, histological examination and gene expression study revealed that the decorated AuNP significantly suppressed c-Myc expression. Thus, we envision that the layer-by-layer assembly on the anionic brushes can be potentially used to incorporate nucleic acids onto metallic particles with high transfection efficiency.